Positive Feedback Investment Strategies and Destabilizing Rational Speculation. - De Long, J Bradford (Journal of Finance, 1990)
Analyses of rational speculation usually presume that it dampens fluctuations caused by "noise" traders. This is not necessarily the case if noise traders follow positive-feedback strategies–buy when prices rise and sell when prices fall. It may pay to jump on the bandwagon and purchase ahead of noise demand. If rational speculators' early buying triggers positive-feedback trading, then an increase in the number of forward-looking speculators can increase volatility about fundamentals. This model is consistent with a number of empirical observations about the correlation of asset returns, the overreaction of prices to news, price bubbles, and expectations. Coauthors are Andrei Shleifer, Lawrence H. Summers, and Robert J. Waldmann.